2023
DOI: 10.1002/pam.22464
|View full text |Cite
|
Sign up to set email alerts
|

The COVID Cash Transfer Study: The Impacts of a One‐Time Unconditional Cash Transfer on the Well‐Being of Families Receiving SNAP in Twelve States

Abstract: There is growing interest in the use of unconditional cash transfers as a means to alleviate poverty, yet little is known about the effects of such transfers in the U.S. This paper reports on the results of a randomized controlled study of a one-time $1,000 unconditional cash transfer in May 2020 to families with low incomes in 12 U.S. states. The families were receiving, or had recently received, Supplemental Nutrition Assistance Program benefits. We examine the impact of the cash transfer on five pre-registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Thus, the credit increased monthly income by nearly 60%, on average. Prior evidence on cash transfers has shown that effects are often larger for households that receive larger transfers relative to income (e.g., Evans et al, 2016 ; Pilkauskas et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the credit increased monthly income by nearly 60%, on average. Prior evidence on cash transfers has shown that effects are often larger for households that receive larger transfers relative to income (e.g., Evans et al, 2016 ; Pilkauskas et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although we expect that, on average, the monthly credit improved the mental health symptoms of parents, some recent studies find null effects of the 2021 CTC on indicators of mental wellbeing ( Collyer et al, 2022 ; Glasner et al, 2022 ). Furthermore, other experimental studies of unconditional cash transfers have found null or negative mental health impacts ( Gennetian et al, 2022 ; Jacob et al, 2022 ; Jaroszewicz et al, 2022 ; Liebman et al, 2022 ; Magnuson et al, 2022 ; Pilkauskas et al, 2023 ). Jaroszewicz et al (2022) propose that receipt of insufficient cash support (some, but not enough) may increase the salience of unmet needs and therefore produce feelings of distress.…”
Section: Why Might the 2021 Monthly Ctc Payments Affect The Mental He...mentioning
confidence: 98%
See 2 more Smart Citations
“…An advantage of cash (over in-kind or a conditional transfer) is that families can use it in ways that are meaningful or needed by them-but this can make it challenging for researchers who study the effectiveness of cash. [85][86][87][88] Researchers need to consider new ways to measure outcomes, perhaps adaptively, where they evaluate different outcomes for different families, to focus on studying effects on outcomes that families say are important to improve after receiving cash transfers. 89 In the United States, work-contingent policies are very popular, as voters and politicians tend to identify the working poor as deserving of assistance.…”
Section: Other Important Income Support Policy Considerationsmentioning
confidence: 99%